David Frank Adjaye Design Thinking: Pendekatan the Unfold Cinematically - Hadi Jaya Putra; Prisca Bicawasti Budi Sutanty; Sarah Nadia (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2022)
Title: David Frank Adjaye’s Design Thinking: The Unfold Cinematically Approach Design thinking is fundamental to every designer because it becomes a strategy that creatively solves design problems. Adjaye, an architect with various degrees and awards, explicitly stated that the approach used was